2022
DOI: 10.1007/s15010-022-01825-8
|View full text |Cite
|
Sign up to set email alerts
|

Differential efficacy and safety of anti-SARS-CoV-2 antibody therapies for the management of COVID-19: a systematic review and network meta-analysis

Abstract: Purpose To assess and compare the relative efficacy and safety of anti-SARS-CoV-2 antibody regimens for COVID-19. Methods This systematic review and random-effects network meta-analysis was conducted according to PRISMA-NMA. Literature searches were conducted across MEDLINE, EMBASE, PubMed, Web of Science, CENTRAL, and CNKI up to February 20th, 2022. Interventions were ranked using P scores. Results Fifty-five RCTs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 84 publications
2
19
0
Order By: Relevance
“…In comparison, Deng et al. found no significant differences in the incidence of mechanical ventilation, ICU admission, and duration of ICU hospitalisation in COVID‐19 patients treated with anti‐SARS‐CoV‐2 antibodies (e.g., monoclonal antibodies and intravenous immunoglobulins) and those in the control group 146 . Furthermore, research by Yu et al.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…In comparison, Deng et al. found no significant differences in the incidence of mechanical ventilation, ICU admission, and duration of ICU hospitalisation in COVID‐19 patients treated with anti‐SARS‐CoV‐2 antibodies (e.g., monoclonal antibodies and intravenous immunoglobulins) and those in the control group 146 . Furthermore, research by Yu et al.…”
Section: Discussionmentioning
confidence: 96%
“…found no significant differences in the incidence of mechanical ventilation, ICU admission, and duration of ICU hospitalisation in COVID‐19 patients treated with anti‐SARS‐CoV‐2 antibodies (e.g., monoclonal antibodies and intravenous immunoglobulins) and those in the control group. 146 Furthermore, research by Yu et al. found that sarilumab was not significantly associated with a reduced risk of invasive mechanical ventilation (RR 1.15; 95%CI, 0.38–3.51), whereas tocilizumab reduced the risk by 21% (RR 0.79; 95%CI, 0.71–0.88).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The low rate of adverse effects observed in our cohort, after mabs and antivirals administration, is in line with data from literature showing - in a real-world evaluation - 1.2% monoclonal antibody infusion-associated adverse events, with 0.3% only considered as severe ( 59 ). In a recent meta-analysis, all mabs demonstrated good safety profiles with no significant increase in adverse events although Casirivimab + imdevimab and sotrovimab were associated with significant reductions in the odds of serious adverse events, with sotrovimab ranking first and casirivimab + imdevimab ranking second in terms of safety ( 60 ). The available evidence of AE is scant regarding antivirals, especially those for at-home therapy, but an incidence comparable with the placebo arm has been reported ( 61 ).…”
Section: Discussionmentioning
confidence: 99%